Comparing molnupiravir and nirmatrelvir/ritonavir efficacy and the effects on SARS-CoV-2 transmission in animal models - Robert M. Cox; Carolin M. Lieber; Josef D. Wolf; Amirhossein Karimi; Nicole A. P. Lieberman; Zachary M. Sticher; Pavitra Roychoudhury; Meghan K. Andrews; Rebecca E. Krueger; Michael G. Natchus; George R. Painter; Alexander A. Kolykhalov; et al. (Nature Communications, 2023)
Abstract Therapeutic options against SARS-CoV-2 are underutilized. Two oral drugs, molnupiravir and paxlovid (nirmatrelvir/ritonavir), have received emergency use authorization. Initial trials suggested greater efficacy of paxlovid, but recent studies indicated comparable potency in older adults. Here, we compare both drugs in two animal models; the Roborovski dwarf hamster model for severe COVID-19-like lung infection and the ferret SARS-CoV-2 transmission model. Dwarf hamsters treated with either drug survive VOC omicron infection with equivalent lung titer reduction. Viral RNA copies in the upper respiratory tract of female ferrets receiving 1.25 mg/kg molnupiravir twice-daily are not significantly reduced, but infectious titers are lowered by >2 log orders and direct-contact transmission is stopped. Female ferrets dosed with 20 or 100 mg/kg nirmatrelvir/ritonavir twice-daily show 1–2 log order reduction of viral RNA copies and infectious titers, which correlates with low nirmatrelvir exposure in nasal turbinates. Virus replication resurges towards nirmatrelvir/ritonavir treatment end and virus transmits efficiently (20 mg/kg group) or partially (100 mg/kg group). Prophylactic treatment with 20 mg/kg nirmatrelvir/ritonavir does not prevent spread from infected ferrets, but prophylactic 5 mg/kg molnupiravir or 100 mg/kg nirmatrelvir/ritonavir block productive transmission. These data confirm reports of similar efficacy in older adults and inform on possible epidemiologic benefit of antiviral treatment.